Thermoelectric properties of La3+ and Ce3+ co-doped CaMnO3 prepared by tape casting. Issue 3 (March 2020) - Kim, C.M.; Kim, D.H.; Hong, H.Y.; Park, K.
Abstract: The structural and thermoelectric transport properties of Ca0.9 La0.1– x Ce x MnO3– δ ( x = 0 – 0.1) prepared through tape casting process were investigated. The thermoelectric transport properties of CaMnO3 were optimized by the La 3+ and Ce 3+ co-doping and tape casting process. The Ce 3+ substitution substantially enhanced the dimensionless figure-of-merit ( ZT ) due to the increases in electrical conductivity and absolute Seebeck coefficient. Of the studied samples, Ca0.9 La0.025 Ce0.075 MnO3– δ had the maximum ZT (0.17) at 800 °C, and this value was 42% and 70% larger than those of singly doped Ca0.9 La0.1 MnO3– δ (0.12) and Ca0.9 Ce0.1 MnO3– δ (0.10), respectively. We demonstrate that both the La 3+ and Ce 3+ co-doping and tape casting process are highly promising approaches in enhancing the high-temperature thermoelectric transport properties of CaMnO3 .